Understanding Student Perspectives on Emergency Remote Teaching: Insights for Enhanced Learning - Sengkey, Virginia Gabrella (SUMIKOLAH: Jurnal Ilmu Pendidikan, 2024)
This study employed descriptive and correlational research designs to investigate how students perceive Emergency Remote Teaching (ERT). Specifically, the study focused on assessing students’ views regarding the effectiveness, attitude, and anxiety levels associated with ERT. Additionally, the study aimed to investigate the relationships between students’ perceived effectiveness of ERT and their levels of satisfaction, as well as the correlation between their attitudes towards ERT and their satisfaction and anxiety levels. The study sample comprised 109 students from a private university in North Sulawesi. The findings revealed that students perceived ERT as highly effective and reported high levels of satisfaction. Furthermore, students displayed a positive attitude towards ERT and exhibited low levels of anxiety. The results also indicated significant correlations between students’ perceived effectiveness of ERT and their satisfaction, as well as between their attitude towards ERT and their satisfaction and anxiety levels.